Virtual educational spaces on the Internet: a reinforcement for traditional training - Francisco José GARCÍA-PEÑALVO; Joaquín GARCÍA CARRASCO (Ediciones Universidad de Salamanca, 2016)
Each day the impact of the information society on all the aspects of our daily lives is becoming more evident. In this sense it may also entail changes in educational techniques, especially in the classic mentality of teaching. Exploring new techniques, methods and tools is a challenge for educators in their attempt to take advantage of these technologies. This article presents a proposal for the creation and configuration of virtual education spaces on the basis of a series of educational software components addressed, on the one hand, to strengthening the teacher's creativity and, on the other, to opening doors to teaching activities on the net, which will complement the classic teaching activities carried out in the classroom. This proposal receives the name Enclave.